Servitisation in the Thai Fashion Industry: A Framework and Process - Kaewngern, Santamol (2016)
Servitisation, the idea that providing additional services with the sale of a product can create value, is regarded as one of the more effective ways through which a company might gain an advantage in the globalised business market. Intangible services can bring manufacturers several benefits, such as high revenue, sustainable business, and uniqueness due to difficulty for other companies to imitate them. This paper proposes a framework through which manufacturers and service providers in Thailand can approach servitisation. Based on the concept that the value of products or services is determined by the customer, it would follow that one can gain a competitive advantage in business by improving the level of customer satisfaction. The comments from the companies on the proposed framework indicate that it is a laborious project requiring both time and resources. Although the framework shows potential in assisting companies with switching from product-centric to service-centric business, it would still require a large amount of preparation on the company’s part.